FOXP1 mutations cause intellectual disability and a recognizable phenotype2. Issue 12 (24th September 2013) - Le Fevre, Anna K.; Taylor, Sharelle; Malek, Neva H.; Horn, Denise; Carr, Christopher W.; Abdul‐Rahman, Omar A.; O'Donnell, Sherindan; Burgess, Trent; Shaw, Marie; Gecz, Jozef; Bain, Nicole; Fagan, Kerry; et al.
Abstract Mutations in FOXP1, located at 3p13, have been reported in patients with global developmental delay (GDD), intellectual disability (ID), and speech defects. Mutations in FOXP2, located at 7q31, are well known to cause developmental speech and language disorders, particularly developmental verbal dyspraxia (DVD). FOXP2 has been shown to work co‐operatively with FOXP1 in mouse development. An overlap in FOXP1 and FOXP2 expression, both in the songbird and human fetal brain, has suggested that FOXP1 may also have a role in speech and language disorders. We report on a male child with a 0.19 MB intragenic deletion that is predicted to result in haploinsufficiency of FOXP1. Review of our patient and others reported in the literature reveals an emerging phenotype of GDD/ID with moderate to severe speech delay where expressive speech is most severely affected. DVD appears not to be a distinct feature in this group. Facial features include a broad forehead, downslanting palpebral fissures, a short nose with broad tip, relative or true macrocephaly, a frontal hair upsweep and prominent digit pads. Autistic traits and other behavioral problems are likely to be associated with haploinsufficiency of FOXP1. Congenital malformations may be associated. © 2013 Wiley Periodicals, Inc.